Teacher's Perspective towards EFL Students' Speaking Performance in Post Covid-19 Pandemic Era - Hilda Fauziyah; Agus Gozali; Putu Dian Danayanti Degeng (Journal of Languages and Language Teaching, 2023)
When learning English, speaking is one of the English skills which is important to learn. Learning to speak will make students able to communicate with others and know what happens in the world. In fact, learning to speak is more challenging than learning other skills in English. In order to speak effectively, students need to practice their speaking regularly. However, the appearance of Covid-19 limits students to practice their speaking face-to-face. After teachers and students adapt to online learning for 2 years, suddenly learning process back to offline learning with certain regulations. Due to that problem, this descriptive qualitative study came up intending to explore the perspective of the teacher regarding EFL students’ speaking performance in the pandemic context and the factors affecting it. Using semi-structured interviews as the instrument, an English teacher who teaches English pre, during, and post-pandemic in SMA Widya Gama Malang has been interviewed in this research. The results of this study revealed that reading material has an impact on students’ speaking performance, the difference in students’ self-confidence during and after the pandemic, students’ willingness to speak during and after the pandemic from the teacher’s perspective, ICT is the best multimedia factor for improving speaking performance, and there is no fixed teaching methodology for teaching speaking.